Potencialna učinkovitost vedenjsko-kognitivne terapije pri obravnavi sorojencev otrok s posebnimi potrebami - Petrič, Mojca (Psihološka obzorja (Ljubljana), 2016)
In this article, we present the empirical findings on psychosocial adjustment of siblings of children with special needs, as well as cognitive-behavioural therapy (CBT) and its techniques as a potential treatment choice. We conclude that most siblings adjust rather well to having a brother/sister with special needs. Still, they are dealing with more challenges and difficulties than siblings of children with typical development, such as having a role of a caregiver, or experiencing stigmatizing interactions with their peers or others, some also develop psychological and/or adjustment problems. There have been some sibling support programs, but little research has been conducted to address their efficacy, and the current findings are contradictory. Considering the challenges the siblings are facing, we believe CBT is a reasonable treatment option.
Keywords: cognitive behavior therapy; vedenjsko kognitivna terapija; posebne potrebe; special needs; children with special needs; otroci s posebnimi potrebami; siblings; sorojenci; psihosocialna prilagojenost; psychosocial adjustment